Comparative study between Valeriana Officinalis L. and diazepam: a literature review - Campos, Gabrielle Soares (2021)
The purpose of this study was to carry out a bibliographic review to compare the efficacy of Valeriana officinalis L. and the benzodiazepine diazepam, in order to control anxiety during the dental treatments, analyzing existing studies in the literature. It was carried out through a literature search using the electronic databases PUBMED, SCIELO, LILACS, COCHRANE BRASIL and EBSCOhost. The descriptors used for selection, both in English and in Portuguese, were conscious sedation, diazepam, Valeriana officinalis L., anxiolytics, benzodiazepines and Dentistry. As a Boolean operator, “and” was used. The articles reached through these search strategies were evaluated and defined as compatible or not, according to their relevance, type of drug application, giving priority to oral use, and also the clarity of ideas in the articles. It was concluded that the use of herbal medicines, such as Vallerina officinalis, by dentists is still little known and explored. Probably for this reason, there is a greater use of benzodiazepines, such as diazepam, as its mechanism of action is well known, as well as its indications and contraindications. Thus, clinical, controlled and double-blind studies are important to give more support to the indications and effectiveness of herbal medicines in relation to dental procedures.